Musicogenetics – A Tool in the Treatment of Leukemia - Uma, A.N.; I., Sharathchandiran. (International Journal of Psychosocial Rehabilitation, 2020)
Down syndrome or Tri 21 has been linked to leukemia and has been published as a case report in 1930. Ever since then, down syndrome has been documented as one of the main leukemia-predisposing syndromes. Reports from researchers, of profound Satellite associations seen in the chromosomes of Down syndrome patients clearly indicate increased DNA damage, signifying vulnerability to leukemia. Since ‘Musicogenetics appears to be an emerging specialized field, as an innovation, Music therapy was given to nine children between the age group of eight months to one year to find out if the DNA damaging profile most predominantly seen in these children decreased, rendering them a hope that they may not be susceptible to leukemia. The frequency of satellite or acrocentric chromosomes in association of the babies was 81% before the music therapy [Veena music] and after three months of 24 music therapy hearings, it was found that the satellite associations fell to a startling 60% indicating that music could play a role in reducing the DNA damage. The mechanism is still unknown, but literature states that the soothing music stimulate calming alpha brain waves, helping to filter out stress, frustration, anxiety and agitation in Down’s syndrome patients in general, helping them to achieve a sense of calmness which may have played a part in reducing the frequency of satellite or acrocentric chromosomes in association. Music therapy treatment at a very early age might provide Down’s syndrome patients with a success-oriented, normal kind of experience, giving them a more optimistic self-image and a life without any gross medical complications in future. Also maybe the reduction of DNA damage due to music therapy may prevent the Down syndrome from the vulnerability to leukemia. More such studies are required before we arrive to a meaningful conclusion.